Exploring medically-related Canadian summer student research programs: a National Cross-sectional Survey Study - Sagar Patel; Catharine M. Walsh; Jacob A. Udell (BMC Medical Education, 2019)
Abstract Background Summer student research programs (SSRPs) serve to generate student interest in research and a clinician-scientist career path. This study sought to understand the composition of existing medically-related Canadian SSRPs, describe the current selection, education and evaluation practices and highlight opportunities for improvement. Methods A cross-sectional survey study among English-language-based medically-related Canadian SSRPs for undergraduate and medical students was conducted. Programs were systematically identified through academic and/or institutional websites. The survey, administered between June–August 2016, collected information on program demographics, competition, selection, student experience, and program self-evaluation. Results Forty-six of 91 (50.5%) identified programs responded. These SSRPs collectively offered 1842 positions with a mean 3.76 applicants per placement. Most programs (78.3%, n = 36/46) required students to independently secure a research supervisor. A formal curriculum existed among 61.4% (n = 27/44) of programs. Few programs (5.9%, n = 2/34) offered an integrated clinical observership. Regarding evaluation, 11.4% (n = 5/44) of programs tracked subsequent research productivity and 27.5% (n = 11/40) conducted long-term impact assessments. Conclusions Canadian SSRPs are highly competitive with the responsibility of selection primarily with the individual research supervisor rather than a centralized committee. Most programs offered students opportunities to develop both research and communication skills. Presently, the majority of programs do not have a sufficient evaluation component. These findings indicate that SSRPs may benefit from refinement of selection processes and more robust evaluation of their utility. To address this challenge, the authors describe a logic model that provides a set of core outcomes which can be applied as a framework to guide program evaluation of SSRPs.